Pesilat Conflict Analysis in Madiun: Conflict Resolution Study - Ximenes, Manuel; Sudarmo, Sudarmo; Setyowati, Kristina (Universitas Pendidikan Ganesha, 2022)
Conflict between members of the pencak silat organization is a conflict phenomenon caused by various sources of conflict involving members of the pencak silat organization so that it creates public security disturbances in the Madiun Regency area. The conflict made the government handle it through various efforts to resolve the conflict. The purpose of this study is to find out how conflict and conflict resolution can be created and run in the Madiun area. The research method is this research using qualitative research methods, which is a type of research that emphasizes drawing conclusions based on the interpretation of a phenomenon or fact. The results showed that the silat conflict that occurred in the Madiun area was more of a horizontal conflict, namely the conflict that occurred only among the fighters in the Madiun area and the cause was due to trivial problems that occurred between the silat fighter and his silat association. Next, to deal with this problem, the local government tries to carry out conflict resolution based on a community governance approach, namely as an integrative and participatory community or community empowerment in the decision-making process. The approach taken by the local apparatus succeeded in reducing the conflict and creating peace, although the resolution of the conflict was not able to eliminate the feelings or desires of the fighters to stop the conflict between them.